The brief cognitive assessment tool (BCAT): cross-validation in a community dwelling older adult sample. (13th August 2014) - MacDougall, Elizabeth E.; Mansbach, William E.; Clark, Kristen; Mace, Ryan A.
ABSTRACT: Background: Cognitive impairment is underrecognized and misdiagnosed among community-dwelling older adults. At present, there is no consensus about which cognitive screening tool represents the "gold standard." However, one tool that shows promise is the Brief Cognitive Assessment Tool (BCAT), which was originally validated in an assisted living sample and contains a multi-level memory component (e.g. word lists and story recall items) and complex executive functions features (e.g. judgment, set-shifting, and problem-solving). Methods: The present study cross-validated the BCAT in a sample of 75 community-dwelling older adults. Participants completed a short battery of several individually administered cognitive tests, including the BCAT and the Montreal Cognitive Assessment (MoCA). Using a very conservative MoCA cut score of <26, the base rate of cognitive impairment in this sample was 35%. Results: Adequate internal consistency and strong evidence of construct validity were found. A receiver operating characteristic (ROC) curve was calculated from sensitivity and 1-specificity values for the classification of cognitively impaired versus cognitively unimpaired. The area under the ROC curve (AUC) for the BCAT was .90, p < 0.001, 95% CI [0.83, 0.97]. A BCAT cut-score of 45 (scores below 45 suggesting cognitive impairment) resulted in the best balance between sensitivity (0.81) and specificity (0.80). Conclusions: A BCAT cut-score can be used for identifying persons to be referred to appropriate healthcare professionals for more comprehensive cognitive assessment. In addition, guidelines are provided for clinicians to interpret separate BCAT memory and executive dysfunction component scores.